60 Years of Pressure in Retrospect. (2015) - Le May, I.
Abstract: The paper outlines the writer's involvement with pressure-related equipment over a period of some sixty years. It highlights some of the achievements of the author and his colleagues originally presented in a plenary lecture at Shanghai during the fourteenth international Pressure Vessel Conference, ICPVT-14, and includes commentary on recent developments in pressure design and analysis.